High Efficiency Extractions of V, Cr, Ti, Fe and Mn from Vanadium Slag by Microwave Heating - Bo, Tan; Shun, Wu; Lijun, Wang; Kuo-chih, Chou (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
The vanadium slag (V-slag) was generated from smelting Vanadium titanomagnetite ore, which contains various valuable elements, such as V, Ti, Cr, Fe and Mn. The traditional methods are more focused on the extractions of V and Cr by oxidation or reduction processes. In the present work, chlorination method was adopted to keep the valence state of each elements as original state to form dissolvable compounds in molten salt. In order to speed up the diffusion of elements, and reduce volatility of molten salt, microwave heating has been examined in the current paper. The results indicated that it only takes 30 min to chlorinate V-slag at 800 °C, and the chlorination ratio of V, Cr, Mn, Fe and Ti can reach to 82.67%, 75.82%, 92.96%, 91.66% and 63.14%, respectively. Compared with the results by conventional heating for 8 h such extraction rate shows great advantages. In addition, microwave heating can reduce volatilization of AlCl3 effectively by shorten the reaction time. The volatilization ratio of AlCl3 is 3.92% instead of 8.97% in conventional heating (1h). The mechanism of high efficient chlorination can be summarized as the enhancement of ions diffusion process and local high temperature enhances chemical reaction.